2008
DOI: 10.1128/aac.00234-08
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus Forms Biofilms with Reduced Antifungal Drug Susceptibility on Bronchial Epithelial Cells

Abstract: Aspergillus fumigatus is a leading cause of death in immunocompromised patients and a frequent colonizer of the respiratory tracts of asthma and cystic fibrosis (CF) patients. Biofilms enable bacteria and yeasts to persist in infections and can contribute to antimicrobial resistance. We investigated the ability of A. fumigatus to form biofilms on polystyrene (PS) and human bronchial epithelial (HBE) and CF bronchial epithelial (CFBE) cells. We developed a novel in vitro coculture model of A. fumigatus biofilm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
207
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(237 citation statements)
references
References 20 publications
22
207
1
7
Order By: Relevance
“…Additionally, both C. krusei and A. fumigatus, have the ability to form biofilms in biomedical devices that come in contact with skin, mucosal or inert surfaces (Quindós et al, 2009;Seidler et al, 2008). Previous studies have reported the reduction of C. albicans biofilms by essential oils (Agarwal et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, both C. krusei and A. fumigatus, have the ability to form biofilms in biomedical devices that come in contact with skin, mucosal or inert surfaces (Quindós et al, 2009;Seidler et al, 2008). Previous studies have reported the reduction of C. albicans biofilms by essential oils (Agarwal et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…This growth phenotype, which complies with the definition of a biofilm (10), may help A. fumigatus to colonize the host substratum and to resist phagocytic and antimicrobial attacks, mimicking the typical Candida albicans or bacterial biofilm (8,11). Recent observations have consistently shown that all antifungal drugs are significantly less effective when A. fumigatus is grown as a biofilm than when it is grown in the planktonic state (4,7,9,12,13), presumably as a reflection of multiple resistance mechanisms, including the ECM, which would prevent drug diffusion by acting as a physical barrier (14). This could contribute to the overall mortality with invasive aspergillosis, which remains high, despite the use of newer broad-spectrum antifungal agents and diagnostic adjuncts (15).…”
mentioning
confidence: 99%
“…S imilar to biofilm-forming bacteria or yeasts (1), Aspergillus fumigatus, the most prevalent airborne fungal pathogen (2), is now largely acknowledged to be an organism able to grow and develop as a multicellular community (3), in which the hyphae are cohesively bonded together by a hydrophobic extracellular matrix (ECM) (4), under the aerial and static conditions found by the fungus either in vitro or in vivo (5)(6)(7)(8)(9). This growth phenotype, which complies with the definition of a biofilm (10), may help A. fumigatus to colonize the host substratum and to resist phagocytic and antimicrobial attacks, mimicking the typical Candida albicans or bacterial biofilm (8,11).…”
mentioning
confidence: 99%
“…Biofilms are complex communities of microorganisms that grow embedded in an extracellular matrix composed of DNA, protein, and exopolysaccharide (7). Biofilm formation provides a significant advantage to these organisms because the matrix mediates adherence to host cells (8,9) and aids in the resistance to both antimicrobial agents (10,11) and host-immune defenses (12,13). A. fumigatus biofilm formation depends on the cationic polysaccharide galactosaminogalactan (GAG), a heteroglycan composed of α1,4-linked galactose and N-acetyl-D-galactosamine (GalNAc) that is partially deacetylated (14,15).…”
mentioning
confidence: 99%